Non-contact capacitive-based water wave sensing system for reservoir surveillance - Soong, Lim Way; Chin, Yeo Boon; Hao, Lim Zhi; Pocherd, Pee; Wei, Lui Poh; Veerapun, Salisa; Waluyo, Dwi Eko; Pramunendar, Ricardus Anggi (Edelweiss Applied Science and Technology, 2025)
Water quality is a major environmental concern and one of humanity’s grand challenges. Many countries face water pollution from oil spills, plastic waste, and illegal activities. Vision cameras are commonly used to monitor reservoirs and dams, but their performance declines between day and night, and they remain fixed in position. Installing numerous cameras to cover every area is costly. Environmental monitoring in remote water sources is further limited by time, cost, and labor. Conventional water monitoring systems often lack intelligence, are bulky, and provide poor real-time results. This research introduces a novel approach using capacitive-based water level sensing to detect patterns and predict types of water activities around an Unmanned Surface Vehicle (USV). The USV operates in real time to monitor illegal activities such as swimming, boating, chemical disposal, and logging in reservoirs and lakes. The system’s innovation lies in a circular array of capacitive sensors that measure water displacement and interpret wave direction and strength. By analyzing these wave patterns, the USV can detect and classify surrounding water activities, providing a cost-effective and intelligent solution for remote water surveillance and pollution prevention.